PENGEMBANGAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM BERBASIS PROBLEM BASED LEARNING UNTUK MENANGKAL RADIKALISME PADA PESERTA DIDIK SMA NEGERI DI KOTA BANDAR LAMPUNG - Syafei, Imam (Universitas Islam Negeri Raden Intan Lampung, 2019)
Through the development of Islamic religious education teaching materials based on problem based learning, it is expected to further enhance the knowledge of Islamic religion of students, so that it is easier for these students to ward off radicalism. The purpose of this study (i) how is the development of Islamic religious education teaching materials based on problem based learning to counteract radicalism in students? (2) how is the effectiveness of Islamic religious education teaching materials based on problem based learning to ward off radicalism in students? So that the main objective in this research is to develop Islamic religious education teaching materials based on problem based learning, so as to ward off radicalism in high school students in Bandar Lampung City. This study uses research and development design, with a sample of 30 high school students in Bandar Lampung, part of the experimental class as a control class. Data collection techniques using questionnaires and documents. The data obtained were then analyzed using gain analysis and independent sample t test. The conclusions of the study are (1) the realization of the development of Islamic religious education teaching materials based on problem based learning to counteract radicalism in high school students in Bandar Lampung City. (2) there is a difference in the attitude of radicalism of students who use it and those who do not use teaching materials based on problem-based Islamic education in state high schools in Bandar Lampung City.